Analisis Faktor yang Mempengaruhi Perataan Laba - Ridwan Ridwan; Fransiska Fransiska (Universitas Muhammadiyah Metro, 2020)
This study aims to examine the influence of factor analysis i.e. profitabilty, financial leverage, company size, public shareholders and liquidity on the income smoothing praxis of coal's sub-sector firm listed on the Stock Exchange in the 2013-2017 years. This research is a associative type. The data source used is secondary data in the form of the company's financial statements. The sampling technique used was purposive sampling, and samples of six coal's sub-sector firms. The data analysis method uses descriptive statistics analysis, panel data regression, the classical assumption test and hypotesis test. The results showed that income smoothing praxis can be influenced by profitabilty, financial leverage, company size, public shareholders and liquidity both simultaneously and partially.